Synchrotron radiation Ca K-edge 2D-XANES spectroscopy for studying the stratigraphic distribution of calcium-based consolidants applied in limestones - Monico, Letizia; Cartechini, Laura; Rosi, Francesca; De Nolf, Wout; Cotte, Marine; Vivani, Riccardo; Maurich, Celeste; Miliani, Costanza (Scientific reports, 2020)
In Heritage Science, the evaluation of stone consolidation treatments by investigating the nature of in situ newly formed products and their penetration depth within the consolidated matrix is a grand challenge. A number of analytical methods have been proposed, but, currently, most of them are not able to supply a full overview of the spatial, structural and compositional information of the newly formed crystalline and amorphous phases with a submicrometric lateral resolution. Here, we examined, the capabilities of synchrotron radiation (SR)-based two-dimensional X-ray absorption near-edge structure (2D-XANES) spectroscopy at Ca K-edge for determining the structural and compositional properties of the compounds formed after the application of a calcium acetoacetate-based consolidant on a porous carbonatic stone (limestone) and for investigating their stratigraphic distribution at the submicrometric scale length. We evaluated advantages and drawbacks of three Ca K-edge 2D-XANES-based approaches: (i) transmission mode full-field-XANES (FF-XANES) imaging; (ii) micro-X-ray fluorescence (μ-XRF) mapping above the Ca K-edge combined with the acquisition of XRF mode μ-XANES spectra at a limited number of spots; (iii) full-spectral µ-XANES (FS µ-XANES) mapping in XRF mode and its variant called selectively induced X-ray emission spectroscopy (SIXES) mapping. Overall, Ca K-edge 2D-XANES spectroscopy provided accurate qualitative and semi-quantitative information on the newly formed calcium carbonates (i.e., amorphous calcium carbonate, vaterite and calcite) and their stratigraphic distribution at the submicrometric scale, thus opening a new scenario to study the carbonatation process of calcium-based consolidants in limestones.